KAJIAN MUTASI GEN PADA DNA MITOKONDRIA (MTDNA) SEBAGAI PREDISPOSISI DIABETES MELITUS - Yuliana, Dewi (Jurnal Ilmiah As-Syifaa, 2012)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated levels of blood glucose  are associated with abnormalities in the metabolism of carbohydrates,  fats, and  proteins.  Diabetes mellitus type 2 (DM type 2) is one of chronic diseases that occur with  increasing number of   patients. The involvement of genetic and environment factors, it make  genetic studies of this disease becomes very important. One form of type 2 diabetes is Maternal Inherited Diabetes and Deafness (MIDD) is caused by a mutation of mitochondrial DNA(mtDNA).Keywords : Mutasi, DNA mitokondria (mtDNA), diabetes mellitus